Investors' Perspective on Various Investment Options - Dr. G. Velmurugan; Dr. R. Subashini; Ms. M. Sandhiya (Research Parks Publishers, 2022)
Investment is the process of investing money in something with the expectation of profit. Investment is not speculation nor gambling; it is a calculated decision based on an analysis of the economy, industry, and company. There are numerous investment avenues available in the market, each with its own unique characteristics, through which investors can invest with the anticipation of making money based on their risk tolerance level. Investment avenues are classified into five categories: low risk, moderate risk, high risk, traditional investment avenues, and emerging investment avenues. These studies' primary purpose has been to ascertain the factors that influence investors' investment decisions. Understanding these elements becomes critical for the subject's growth and to assisting professionals in directing investors toward sound investment selections. Based on available literature, this study attempts to explain the elements that influence individual investors' investment decisions.